SOS chromotest and mutagenicity in Salmonella: evidence for mechanistic differences - Rosenkranz, Herbert; Mersch-Sundermann, Volker; Klopman, Gilles (Mutation research. Fundamental and molecular mechanisms of mutagenesis, 1999)
An examination of the relationship of the experimental results obtained with chemicals tested in the SOS chromotest and for mutagenicity in Salmonella indicates that the two assays respond to different genotoxic stimuli. Furthermore, the relationship between results obtained in these assays and in rodents carcinogenicity bioassays suggests that the short-term assays respond to a different spectrum of carcinogens. The same conclusions were reached based upon an analysis of the structural features associated with these three phenomena. With respect to using these short-term assays to predict carcinogens, the present results suggest that they are not equivalent, but complement one another.
Elektronische Reproduktion der Druckausgabe
Gesehen am 27.05.2022